Analysing the Impact of Hotels Customer Relationship Management Strategies on Customers Hotel Selection in Bhopal City ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: The choice of the hotel is shaped by Customer relationship management strategies commonly termed  as CRM. CRM is therefore essential to positively influence purchase decisions of hotel guests, retaining travelers and  satisfying the customers, or else risks driving them away. Objectives: The first objective of the study was to identify  the key CRM strategies exercised by hotels to influence customer’s hotel selection. The second objective of the study  was to analyze the key influence of important hotels CRM strategies on customer’s hotel selection. Methodology: The  study focuses on star-category hotels in Bhopal, with data collected from travelers over 18 years using convenience  sampling. A structured questionnaire, distributed via Google Forms, gathered primary data on demographic profiles  and key CRM strategies, with responses rated on a five-point Likert scale. Secondary data came from reports, research  papers, and articles. Data was collected in July and August 2024. The first objective, identifying key CRM strategies,  was addressed through previous studies, while the second objective, analyzing CRM’s influence on hotel selection,  was achieved using weighted mean scores. Results: After extensive study of previous literature, key CRM strategies  found were personalized guest experiences, loyalty programs, staff training and empowerment, events and activities,  special offers and promotions, efficient booking processes, pre-arrival communication, in-room technology, dynamic  pricing, social media engagement and post-stay follow-up. The second objective results indicated that staff training and  empowerment had the highest influence on customer hotel selection, with a weighted mean score of 3.25, followed by  special offers and promotions (3.23), and dynamic pricing (3.22). Conclusions: These factors will afford a prescription  for enhancing customer acquisition and retention in the context of the hotel organization.
Keywords: Bhopal City; CRM strategies; hotel industry; customer’s hotel selection